Data from: Subarctic singers: Humpback whale (Megaptera novaeangliae) song structure and progression from an Icelandic feeding ground during winter ... - Magnúsdóttir, Edda E.; Lim, Rangyn (Dryad, 2019)
Humpback whale songs associated with breeding behaviors are increasingly reported outside of traditional low latitude breeding grounds. Songs from a subarctic feeding ground during the winter were quantitatively characterized to investigate the structure and temporal changes of the songs at such an atypical location. Recordings were collected from 26. January to 12. March, 2011, using bottom mounted recorders. Humpback songs were detected on 91% of the recording days with peak singing activities during 9.–26. February. The majority of the recordings included multiple chorusing singers. The songs were characterized by a) common static themes which transitioned consistently to predictable themes, b) shifting themes which occurred less predictably and c) rare themes. A set median sequence was found for four different periods (sets) of recordings (approximately 1 week each). The set medians were highly similar and formed a single cluster indicating that the sequences of themes sung in this area belonged to a ... : Metadata - Phrases and total song detectionsThe spread sheet contains 4 different datasets each located in a separate sheet. The first sheet contains all the acoustic sound files detected with the automatic humpback whale song detector ("All_detections"). In the second sheet named "Phrases" there is a subsample of humpback whale song files which was created from the whole dataset. This subsample was used to analyse phrase occurrence and sequences of phrases. The third sheet named "AnalysedSoundFiles_subsample" contains a random subsample of sound files from the sheet "Phrases". This subsample was used to measure the average signal to noise ratio of the song units in the sound files, including the average received signal level to investigate differences in these values in analysed sound files between periods within the total study period. The forth sheet named "TotalFiles_Randosubsample" contains a random subsample of the total detected files from the sheet "All_detections". That data was used to investigate ...